2007
DOI: 10.1634/stemcells.2006-0688
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Progenitor Cell Mobilization Results in Hypoxia with Increased Hypoxia-Inducible Transcription Factor-1α and Vascular Endothelial Growth Factor A in Bone Marrow

Abstract: Despite the fact that many hypoxia-inducible genes are important in hematopoiesis, the spatial distribution of oxygen in the bone marrow (BM) has not previously been explored in vivo. Using the hypoxia bioprobe pimonidazole, we showed by confocal laser scanning microscopy that the endosteum at the bone-BM interface is hypoxic, with constitutive expression of hypoxia-inducible transcription factor-1␣ (HIF-1␣) protein in steady-state mice. Interestingly, at the peak of hematopoietic stem and progenitor cell (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 68 publications
5
115
0
2
Order By: Relevance
“…Indeed, two recent studies agree with this notion, and thus HSCs from mouse BM are the most positive for binding of the hypoxic probe pimonidazole [9], which coincides with low levels of intracellular ROS [10]. Using pimonidazole as a marker for hypoxia, it has also been shown that hypoxic areas in the BM seem to correlate with the endosteal space [11]. Furthermore, slow-cycling cells are located in hypoxic regions containing sinusoids without capillary structures [12].…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, two recent studies agree with this notion, and thus HSCs from mouse BM are the most positive for binding of the hypoxic probe pimonidazole [9], which coincides with low levels of intracellular ROS [10]. Using pimonidazole as a marker for hypoxia, it has also been shown that hypoxic areas in the BM seem to correlate with the endosteal space [11]. Furthermore, slow-cycling cells are located in hypoxic regions containing sinusoids without capillary structures [12].…”
Section: Introductionmentioning
confidence: 77%
“…The circulating fraction of these cells can be increased by process named mobilization. The pharmacological mobilization of hematopoietic stem and progenitor cells is usually obtained by using cyclophosphamide in combination with myeloid growth factors, which enhance the effect of chemotherapeutic agent [3,5,6,16]. Although the molecular mechanism of mobilization is widely examined, the morphology of the bone marrow and organs, which participate in hematopoiesis in mice, is poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF induces accumulation of proteases released from neutrophils into the extravascular compartment of BM. These proteases degrade and inactivate adhesive and chemotactic interactions between HSPC and the BM stromal cells, particularly VCAM-1, CXCR4 and its ligand SDF-1, decreasing affinity of CXCR4/SDF-1 axis [3][4][5][6][7]. A pivotal role in the mobilization of HSPC is attributed to complement system and egress of HSPC from the BM is thought as a part of an immune response [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that while BMderived EPCs contribute to early angiogenic switch, once neovascularisation is established, the traffic of these cells is limited and extra-medullary processes perpetuate the local tissue neovascularisation process (13,14). It is possible, that targeting of the lung-homing and local proliferative potential of EPCs in pulmonary tissue could modulate airway remodelling in COPD, however additional research is needed to clarify.…”
Section: Epcsmentioning
confidence: 99%